Magnetic, Spectral, Thermal and Electrical Properties of Manganese, Cobalt, Nickel, Copper and Zinc Polychelates of 4,4-Dihydroxy-3,3-dipropionyl biphenyl-(3,4-diaminoanisole) - Kumar, Ashwini (Asian Journal of Chemistry, 2010)
Metal polychelates of the type [ML(H2O)2] where M = Mn(II) Ni(II), Cu(II), Zn(II) an.' H2L = 4,4'-dibydroxy-3,3'-dipropionyl biphenyl- (3,4-diaminoanisole) have been sythesized. Their structures have been elucidated on the basis of analytical, magnetic, electric and spectral study as well as elemental analysis. D.C. electrical conductivity has been measured over a temperature range 400-425 K. The ligand and its polychelates have also been screened for their antimicrobial activity using various microorganisms.